A highly effective "naked eye" colorimetric and fluorimetric curcumin-based fluorescent sensor for specific and sensitive detection of H2O2in vivo and in vitro. Issue 8 (20th March 2023) - Du, Wenhao; Shen, Zheyu; Liang, Yueying; Gong, Shuai; Meng, Zhiyuan; Li, Mingxing; Wang, Zhonglong; Wang, Shifa
Abstract : Hydrogen peroxide (H2 O2 ) is involved in many important tasks in normal cell metabolism and signaling. Abstract : Hydrogen peroxide (H2 O2 ) is involved in many important tasks in normal cell metabolism and signaling. However, abnormal levels of H2 O2 are associated with the occurrence of several diseases. Therefore, it is important to develop a new method for the detection of H2 O2 in vivo and in vitro . A turn-off sensor, 2, 2-difluoro-4, 6-bis(3-methoxy-4-((4-(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)benzyl)oxy)styryl)-2 H -1, 3, 2-dioxaborine (DFCB ), based on curcumin was developed for the detection of H2 O2 . The DFCB, an orange-emitting sensor, was constructed by employing 2, 2-difluoro-4, 6-bis(4-hydroxy-3-methoxystyryl)-2 H -1, 3, 2-dioxaborine (DFC ) as the main carrier, and 2-(4-bromomethylphenyl)-4, 4, 5, 5-tetramethyl-1, 3, 2-doxaborolane as the recognition site. The recognition group on the DFCB sensor could be completely cleaved by H2 O2 to generate the intermediate DFC, which would lead to a colorimetric change from bright orange to light blue accompanying by a significantly quenched fluorescence, which could be seen by the naked eye. This sensor exhibited a highly specific fluorescence response to H2 O2, in preference to other relevant species, with an excellent anti-interference performance. The sensor DFCB also possessed some advantages including a wide pH response range (6–11), a broad linear range (0–300 μM), and a low detection limit (1.31 μM). The sensing mechanism of the DFCB sensor for H2 O2 was verified by HRMS analysis, 1 H-NMR titration and DFT calculations. In addition, the use of the DFCB sensor was compatible with the fluorescence imaging of H2 O2 in living cells and zebrafish.